Why the fruit picker smiles in an anti-corruption story: Analyzing evaluative clash and news value construction in online news discourse in China. (June 2020) - He, Juan; Caple, Helen
Highlights: Visual Positivity provides an ideological stance to the negative story. The divergent coupling of headline and image invokes the Socialist Core Values. Visual resources enhance, contradict or complement their linguistic partners. Abstract: In China's journalism, positive photographs are preferred in reporting on negative news stories and such divergent couplings of text and image are crucial in newsworthiness mediation in helping readers understand social values in China. Drawing on Discursive News Value Analysis and appraisal, this article investigates the construal of Negativity and Positivity through evaluative resources across visual-verbal semiotic modes in China's English-language news discourse. Sourced from China Daily and People's Daily online websites, 34 news reports featuring evaluative clash are studied by combining corpus semantic tagging method and manual analysis from both the text-as-corpus and text-as-text approaches. The findings show that Negativity is largely and strategically construed through negative lexis and evaluative language towards news participants like China, the US and Australia in international disputes, while visual Positivity plays an important role in orienting readers to the Socialist Core Value of "Harmony" against the negative news stories through their interplay in the heading-image nucleus. Underlying journalistic positions are revealed through close analysis of news value co-construction in three news stories about national issues, in which visual devices are employed to enhance, contradict or complement the linguistic expressions around social value building.